2018
DOI: 10.1007/s00192-018-3649-8
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of obstetric anal sphincter injury incidence between an Asian and Western hospital

Abstract: The incidence of OASIS in Asian women is significantly higher in a Western than in an Asian setting. In Asian women, perineal length and birthweight can affect the risk of OASIS at the time of vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…Either firm pressure or pressure with squeezing of the perineum, also known as the modified Ritgen manoeuvre, was used. 6 Warm compresses were not commonly used by midwives and doctors in our study.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Either firm pressure or pressure with squeezing of the perineum, also known as the modified Ritgen manoeuvre, was used. 6 Warm compresses were not commonly used by midwives and doctors in our study.…”
Section: Discussionmentioning
confidence: 66%
“…Compared with previous studies, the rate of OASIS determined by endoanal US in our study (6.5%) was lower than the rate of 10% determined by a single examiner in a prospective observational study conducted in the same unit. 6 This could be a result of the small sample size (70 subjects) in the prior study. Furthermore, most patients with OASIS (5/7) in that study were reported to have small 3a tears.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations